Digital Transformation Of Islamic Education In Pondok Pesantren Darunnajah: Integration Of Islamic Values And Technology Literacy In Facing The Society 5.0 Era - Sofwan Manaf; Ahsanul Mufid; Rokimin; Nesa Novrizal (Qoumun: Jurnal Pengabdian Masyarakat, 2026)
Purpose of the study: This study aimed to investigate the digital transformation of Islamic education within pesantren (Islamic boarding schools), focusing on the integration of Islamic values and technology literacy as a strategic response to Society 5.0, while addressing the unique challenges pesantren face in integrating modern technology while preserving their foundational Islamic values. Methodology: An integrative literature review methodology was employed, synthesizing findings from 35 peer-reviewed articles published between 2020 and 2025, sourced from reputable databases including Scopus, Web of Science, and SINTA-accredited journals. Main Findings: The analysis reveals three principal findings: first, pesantren leaders (kiai) increasingly demonstrate receptive attitudes toward digital adoption while maintaining Islamic epistemological frameworks; second, the integration of technology literacy within pesantren curricula produces synergistic outcomes when anchored in Islamic ethical principles such as amanah (trustworthiness), maslahat (common good), and tawazun (balance); and third, persistent challenges including infrastructural limitations, digital literacy disparities among educators, and cultural resistance necessitate a phased, values-driven transformation model. Novelty/Originality of this study: The novelty lies in the proposal of the Pesantren Digital Integration Framework (PDIF), a conceptual model that harmonizes technological modernization with the preservation of pesantren identity and Islamic pedagogical traditions specifically anchored in Islamic ethical principles (amanah, maslahat, tawazun) addressing the underexplored intersection of digital transformation and traditional Islamic education within the Society 5.0 context, an integrated approach not previously documented in pesantren settings.